The origin of bmp16, a novel Bmp2/4relative, retained in teleost fish genomes - Feiner, N; Begemann, G; Renz, A; Meyer, A; Kuraku, S (BioMed Central, 2009)
Background: Whole genome sequences have allowed us to have an overview of the evolution of gene repertoires. The target of the present study, the TGFβ superfamily, contains many genes involved in vertebrate development, and provides an ideal system to explore the relationships between evolution of gene repertoires and that of developmental programs. Results: As a result of a bioinformatic survey of sequenced vertebrate genomes, we identified an uncharacterized member of the TGFβ superfamily, designated bmp16, which is confined to teleost fish species. Our molecular phylogenetic study revealed a high affinity of bmp16 to the Bmp2/4 subfamily. Importantly, further analyses based on the maximum-likelihood method unambiguously ruled out the possibility that this teleost-specific gene is a product of teleost-specific genome duplication. This suggests that the absence of a bmp16 ortholog in tetrapods is due to a secondary loss. In situ hybridization showed embryonic expression of the zebrafish bmp16 in the developing swim bladder, heart, tail bud, and ectoderm of pectoral and median fin folds in pharyngula stages, as well as gut-associated expression in 5-day embryos. Conclusion: Comparisons of expression patterns revealed (1) the redundancy of bmp16 expression with its homologs in presumably plesiomorphic expression domains, such as the fin fold, heart, and tail bud, which might have permitted its loss in the tetrapod lineage, and (2) the loss of craniofacial expression and gain of swim bladder expression of bmp16 after the gene duplication between Bmp2, -4 and -16. Our findings highlight the importance of documenting secondary changes of gene repertoires and expression patterns in other gene families.